2012
DOI: 10.1016/j.materresbull.2011.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Size and defect related broadening of photoluminescence spectra in ZnO:Si nanocomposite films

Abstract: Nanocomposite films of Zinc Oxide and Silicon were grown by thermal evaporation technique using varying ratios of ZnO:Si in the starting material. Analysis reveal the role of ZnO and amorphous silicon interface in contributing to relatively less common blue photoluminescence emissions (at ∼ 400 and 470nm). These blue peaks are observed along with the emissions resulting from band edge transition (370nm) and those related to defects (522nm) of ZnO. Careful analysis shows that along with the grain size of ZnO, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Undoped ZnO gives emission in the UV at 374 nm (3. [32]. In our study these reasons are supported by XRD and AFM results which show that crystallite size is very small that increases number of grain boundaries.…”
Section: Photoluminescencesupporting
confidence: 77%
“…Undoped ZnO gives emission in the UV at 374 nm (3. [32]. In our study these reasons are supported by XRD and AFM results which show that crystallite size is very small that increases number of grain boundaries.…”
Section: Photoluminescencesupporting
confidence: 77%
“…Many existing studies have already intensively reported on the various fabrication techniques and optical properties of ZnO-NCs embedded in SiO 2 [5-15]. Nonetheless, a complete investigation on the growth of ZnO-NCs as a function of annealing temperature under different annealing environments is essential to understand the influence of various annealing conditions on the optical properties of ZnO-NC:SiO 2 systems.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of curves in fig 2 suggests that the defects increase in ZnO grains with film thickness and conversely the perfect wurtzite crystal structure decreases. Earlier works have shown that existence of comparable contribution of 370 and 520 nm and inturn amount of lattice with and without defects is a crucial factor to obtain broadening in PL spectra [4,5]. The region of intersection of the two curves of fig 2, namely the range 60-90 nm, marks the sample thickness that would potentially give broad emissions (here sample 'c60', see fig 1).…”
Section: Resultsmentioning
confidence: 95%